Edge or Cloud Architecture: The Applicability of New Data Processing Methods in Large-Scale Poultry Farming - Gergo Toth; Sandor Szabo; Tamas Haidegger; Marta Alexy (Technologies)
As large-scale poultry farming becomes more intensive and concentrated, a deeper understanding of poultry meat production processes is crucial for achieving maximum economic and ecological efficiency. The transmission and analysis of data collected on birds and the farming environment in large-scale production environments using digital tools on a secure platform are not straightforward. In our on-site research, we have investigated two architectures, a cloud-based processing architecture and an edge computing-based one, in large-scale poultry farming circumstances. These results underscore the effectiveness of combining edge and cloud-based solutions to overcome the distinct challenges of precision poultry farming settings. Our system’s dynamic capability, supported by AWS’s robust cloud infrastructure and on-site edge computing solutions, ensured comprehensive monitoring and management of agricultural data, leading to more informed decision-making and improved operational efficiencies. A hybrid approach often represents the most viable strategy when examining contrasting strengths and weaknesses. Combining edge and cloud solutions allows for the robustness and immediate response of edge computing while still leveraging cloud systems’ advanced analytical capabilities and scalability.